2012
DOI: 10.1016/j.neuroscience.2012.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in reward-seeking following morphine withdrawal are associated with altered N-methyl-d-aspartate receptor 1 splice variants in the amygdala

Abstract: The NR1 subunit of the NMDA receptor can be alternatively spliced by the insertion or removal of the N1, C1, C2, or C2′ regions. Morphine dependence and withdrawal were previously demonstrated to lower N1 and C2′ in the accumbens and lower N1, C1, and C2′ in the amygdala. Withdrawal has also been demonstrated to increase motivational and anxiety/stress behaviors in rats. We tested the hypothesis that NR1 splicing would be associated with these behaviors during an extended withdrawal period of two months. Motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Similar treatment in rat pups also impaired the adult cognitive functioning (McPherson et al, 2007) as demonstrated by (1) impaired passive avoidance learning (test classically used to assess learning and memory mediated by amygdala), (2) conditioned place preference (mediated by the mesolimbic dopamine system (Prus et al, 2009)), and (3) the forced swimming learning paradigms (which involve serotonergic system (Petit‐Demouliere et al, 2005)). Early life‐prolonged opioid exposure is also associated with long‐term effect such as: decreased analgesia, increased pain sensitivity (Zhang and Sweitzer, 2008), and hypersensitivity to adverse/stress conditions (Anderson et al, 2012). However, these studies did not investigate underlying cellular neuroplasticity that might explain reported behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar treatment in rat pups also impaired the adult cognitive functioning (McPherson et al, 2007) as demonstrated by (1) impaired passive avoidance learning (test classically used to assess learning and memory mediated by amygdala), (2) conditioned place preference (mediated by the mesolimbic dopamine system (Prus et al, 2009)), and (3) the forced swimming learning paradigms (which involve serotonergic system (Petit‐Demouliere et al, 2005)). Early life‐prolonged opioid exposure is also associated with long‐term effect such as: decreased analgesia, increased pain sensitivity (Zhang and Sweitzer, 2008), and hypersensitivity to adverse/stress conditions (Anderson et al, 2012). However, these studies did not investigate underlying cellular neuroplasticity that might explain reported behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased pain sensitivity [39], altered anxiety and stress responses, metabolic changes [40], and potential memory changes (through amygdalo-frontal circuits) [11] have also been reported. These changes may also reflect an overall hypersensitivity and maladaptation to adverse conditions [41] in premature infants. It is however, well established that prematurity alone is associated with numerous neurological sequelae [42], including high risk for cerebral injuries such as hypoxia–ischemia events, stroke, and periventricular leukomalacia [43] implicating prematurity as a significant confounding factor in evaluating neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…An example of the data collected is presented in Figure 1C . The use of the OPAD assay has been described extensively in our previous publications ( Neubert et al, 2005 ; Neubert et al, 2006 ; Neubert et al, 2007 ; Neubert et al, 2008 ; Rossi and Neubert, 2008 ; Rossi et al, 2009 ; Caudle et al, 2010 ; Kumada et al, 2012 ; Nolan et al, 2011 ; Anderson et al, 2012a ; Anderson et al, 2012b ; Nolan et al, 2012 ; Ramirez and Neubert, 2012 ; Rossi et al, 2012 ; Anderson et al, 2013 ; Mustafa et al, 2013 ; Anderson et al, 2014 ; Anderson et al, 2015 ; Ramirez et al, 2015 ; Bowden et al, 2017 ; Caudle et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%